Are infections in children with juvenile idiopathic arthritis more frequent than in healthy children? A prospective multicenter observational study - Clara Udaondo; Clara Udaondo; Clara Udaondo; Esmeralda Núñez Cuadros; Sara Murias; Agustin Remesal; Rosa Alcobendas; Concepción Guerrero; Sara Guillen-Martin; Sara Guillen-Martin; Marta Escuredo; Esther Aleo; et al. (Frontiers Media S.A., 2022)
BackgroundChildren with juvenile idiopathic arthritis (JIA) might be at a higher risk of infection. Our objectives are to describe and compare infection rates in patients with JIA vs. healthy patients.MethodsA prospective, multicenter observational study was performed in Spain from January 2017 to June 2019. Patients with JIA from 7 participating hospitals and children without JIA (siblings of patients with JIA, and non-JIA children from primary health centers) were followed up with quarterly questionnaires to record infection episodes. Tuberculosis, herpes zoster, and infections requiring hospital admission were considered severe infections. Rates of infection (episodes/patient/year) were compared using a generalized estimating equations model.ResultsA total of 371 children (181 with and 190 without JIA) were included. The median age was 8.8 years (IQR 5.5-11.3); 75% of the patients with JIA received immunosuppressive treatment (24% methotrexate, 22% biologic, 26% both). A total of 667 infections were recorded; 15 (2.2%) were considered severe. The infection rate was 1.31 (95%CI 1.1-1.5) in JIA and 1.12 (95%CI 0.9-1.3) in non-JIA participants (p = 0.19). Age <4 years increased the infection rate by 2.5 times (2.72 vs. 1.12, p < 0.001) in both groups. The most frequent infection sites were upper respiratory (62.6% vs. 74.5%) and gastrointestinal (18.8% vs. 11.4%). There were no differences in severe infections (2.5% vs. 2%, p = 0.65) between the groups. In children with JIA, younger age and higher disease activity (JADAS71) were associated with a higher infection rate.ConclusionWe found no differences in the infection rate or infection severity between patients with and without JIA. Most infections were mild. An age younger than 4 years increased the infection risk in both groups. Higher disease activity was associated with a higher infection rate.